Polymers Coatings Technology and Applications. - Inamuddin (John Wiley & Sons, Incorporated, 2020)
The explores the cutting-edge technology of polymer coatings. It discusses fundamentals, fabrication strategies, characterization techniques, and allied applications in fields such as corrosion, food, pharmaceutical, biomedical systems and electronics. --